ChemInform Abstract: Catalytic Hydrogenation of Amino Acids to Amino Alcohols with Complete Retention of Configuration. Issue 46 (18th November 2014) - Tamura, Masazumi; Tamura, Riku; Takeda, Yasuyuki; Nakagawa, Yoshinao; Tomishige, Keiichi
Abstract using a rhodium/molybdenum mixed oxide on silica as effective heterogeneous catalyst